Pengaruh Job Crafting terhadap Work Engagagement melalui Psychological Meaningfulness Karyawan PT Boma Bisma Bisma Indra (Persero) Surabaya - Syah, Nofan Darma (Jurnal Ilmu Manajemen, 2020)
The purpose of this research was to analyze and examine the effect of job crafting on work engagement through the psychological meaningfulness of employees at PT. Boma Bisma Indra (Persero) Surabaya. This research is causality research with a quantitative approach. The number of samples was 55 employees. Statistical analysis using Partial Least Square with SmartPLS 3.0. The results of the study explained that job crafting has a positive and significant influence on work engagement through psychological meaningfulness as a mediator. In addition, the mediating effect also has a better effect than the direct effect.